INDIGENOUS KNOWLEDGE IN LIVESTOCK MANAGEMENT IN AFRICA: A SHORT REVIEW - OSENI, S.O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This review discusses practices, some of which have been validated by scientific methods or least proven to be partially effective and those that have not been tested. The paper revealed how such indigenous practices effect livestock management, health-care and production system. Some unique advantages inherent in such practices were also highlighted. It is recommended that these techniques, particularly those connected with animal health be further validated and refined through formal scientific procedures.